The factors effecting the grade of academicians’ satisfaction level: The reality of major field of study for classroom training - (:unkn) unknown (Ankara University, 2020)
The aim of the research is to find out the satisfaction levels of the academicians in the main science branch of class education; management and organizing, education, research, infrastructure and stakeholder relations subscales according to some demographic variables. Mixed method, explicative sequential pattern was used in the research. A sample of 21 academics working at the university, identified as easily accessible, constitutes the working group, with five academics identified according to the criteria sample of the purposeful sample. Quantitative data were collected through the "Mehmet Akif Ersoy University Academic Staff Satisfaction Survey" and qualitative data were collected through semi-structured interview form. Quantitative data were analyzed by SPSS program and qualitative data by descriptive analysis method. When the findings are examined; the level of satisfaction of academicians did not make a meaningful difference according to their titles, and they showed according to their genders. In addition, the most positive opinion of academicians was sub-dimension, while the most negative was infrastructure. The quantitative findings obtained were examined in depth and the direct opinions of academicians were included. The research was discussed within the framework of related literature and similar study findings and various suggestions were made. © 2020, Ankara University. All rights reserved.
Keywords: Education; Primary education; The quality in higher education; Training teacher